Notice of a Collection of Flint Arrowheads and Implements found on the Farm of Overhowden, in the Parish of Channelkirk, Berwickshire, exhibited to the Society - Sharp, James (Proceedings of the Society of Antiquaries of Scotland, 1912)
The collection consists of 17 lop-sided arrowheads of black flint; 16 worked triangular flakes which may be intended for arrowheads; a large triangular spearhead; 4 arrowheads with barbs and stem; 3 leaf-shaped arrowheads; 14 scrapers; 2 large side-scrapers; 3 whorls; 1 polished hammer, broken across at the middle; 1 globular hammer-stone, and a number of flakes of flint of no definite character. They were entirely found on the farm of Overhowden, with the exception of one small leaf-shaped arrowhead, which was found near Heriot, and an arrowhead of American origin.